Edukasi Layanan Bimbingan dan Konseling Kelasikal untuk Mengentaskan Bahaya Narkolema di Era Revolusi Industri 4.0 Society 5.0 Abad 21 - Lase, famahatolase (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
The dangers of narcotics through the eyes (narcolemma) in the era of industrial revolution 4.0 and society 5.0 in the 21st century are hitting the millennial generation throughout the world. The aim of this research is to solve the problem of the dangers of narcolemma using a descriptive qualitative literature review research method. The research instrument is the researcher himself, data is collected from the source using library study techniques and analyzed using content analysis techniques. The research population was all participants in counseling services and a total sampling of 75 people was drawn. The results of the research reveal that the implementation of classical counseling services has succeeded in guiding each service participant: (1) actively think creatively, feel thoughtfully, have a positive attitude, act responsibly and responsibly to completely prevent and eradicate the dangers of narcolemma; (2) provide an understanding of the dangers, basic concepts, levels of exposure, addiction, consequences, the desire to imitate the pornography watched, the urge to commit sexual acts, BMB3 strategies, and (3) take a positive attitude, make the right decisions, act swiftly to prevent and alleviating the dangers of narcolemma.